PEMBINAAN ADMINISTRASI GURU BERBASIS KURIKULUM 2013 OLEH KEPALA SEKOLAH - Imantoro Imantoro; Rambat Nur Sasongko; Osa Juarsa (UNIVERSITAS BENGKULU, 2017)
The general objective of this study was to describe the teacher administration based on implementation of the 20113 curriculum by the principal at the public school in the city of Bengkulu. This study used descriptive qualitative method. Subjects were principals, teachers, homeroom, teachers, and students. The technique of collecting data using interviews, observation, and documentation. Analysis of data using qualitative techniques. The results showed the administration based teacher development curriculum in 2013 at SDN 1 implemented by reason of administrative requirements for teachers is one of the components that determine the quality of learning of teachers in implementing the curriculum in 2013. With the completion of the classroom teacher administration will be more focused, more organization, more integrated, and finally the teacher will make learning more effective and more efficient.